Identifying the predictors of ultra early neurological improvement and its role in functional outcome after endovascular thrombectomy in acute ischemic stroke - Lai, Yuzheng; Mofatteh, Mohammad; Baizabal-Carvallo, José Fidel; He, Jianfeng; Wu, Wenhao; Wang, Daohong; Yan, Wenshan; Ma, Jicai; Zhou, Sijie; Sun, Yu; He, Yi; Li, Shumei; et al. (Frontiers in Neurology, 2025)
Background and purposeUsing post-treatment methods to predict functional outcomes of acute ischemic stroke (AIS) patients undergoing endovascular thrombectomy (EVT) is crucial in stroke medicine. The National Institute of Health Stroke Scale (NIHSS) score at 24 h has been widely used; however, there is a paucity of data on using earlier NIHSS scores and their association with outcome. In this study, we aimed to investigate the usage of NIHSS at 1-h time window -ultra-early neurological improvement (UENI)- as a surrogate marker associated with the functional outcomes of AIS patients treated with EVT.MethodsWe included 485 adults (≥18 years old) who underwent emergency EVT at four academic comprehensive stroke centers between 2020 and 2021. Patients with pre-EVT Alberta Stroke Program Early CT Score (ASPECTS) < 6, missing follow-up data, and missing data of the first hour NIHSS were excluded (n = 20). UENI was defined as post-EVT NIHSS reduction of 4 points or more or NIHSS as 0–1 within 1-h post-EVT. An mRS score of 0–2 after three months was defined as favorable outcome, and independent walking independence was defined as mRS of 3.ResultsA total of 465 patients were included in our final analysis. We identified 122 (26.2%) patients with UENI. While 82.79% of the patients with UENI achieved favorable functional outcomes at 3-months, only 32.36% of patients without UENI had favorable functional outcome (p < 0.0001). In addition, lower hospitalization costs were associated with patients who had UENI, compared to No-UENI (p = 0.003). A multivariate logistic regression analysis revealed that younger age (p < 0.0001), shorter last know normal to puncture time (LKNPT) (p = 0.013), higher pre-treatment ASPECTS (p = 0.039), final modified thrombolysis in cerebral infarction (mTICI) ≥2b (p = 0.002), and fewer number of EVT attempts (p = 0.002) were variables independently associated with UENI. The presence of UENI was independently associated with a better outcome OR: 7.999 (95% C.I. 4.415–14.495).ConclusionUENI was observed in about a quarter of patients with AIS undergoing EVT. Younger age, shorter LKNPT, higher pre-treatment ASPECTS, final mTICI≥2b, and fewer number of EVT attempts, were independently associated with UENI. The presence of UENI was independently associated with better functional outcome at 3 months.